Reconsidering the Cultural Geographies ofState and non State Spaces (Kawalu: Journal of Local Culture, 2024)
In Indonesia, the societies have a long history as a runaway societyand fugitive from the state-making projects. Many historical accounts provethat people escape from the state projects, such as corvee labor, wars,diseases and epidemics, conscriptions, slavery, taxes, violence, warfare,diseases, and poverty. In general, this paper describes the state-societyrelations and examines the meaning of the non-governed society. This paperquestions what distinguishes between govern and non-governed society,what kind of social economy and cultural life of non-governed society thatdistinguishes from a governed state? To answer these questions, this paperexplores the distinction of the governed and the non-governed society,which live in the different geographical areas. This paper explains thedistinctions and frictions between lowland and highland society inIndonesia, in terms of social economy, kinship, political organization, andreligion. In the last reflection, the author argues that non governed societyis not only people who live in the upland and far from the centralizedbureaucracy, rather they also live in the middle of dense population of atown and even under a most centralized and autocratic regime.